2019
DOI: 10.1016/j.heliyon.2019.e02818
|View full text |Cite
|
Sign up to set email alerts
|

The cell-based approach in neurosurgery: ongoing trends and future perspectives

Abstract: ObjectiveExamination of the current trends and future perspectives of the cell-based therapies in neurosurgery.MethodsA PubMed/MEDLINE-based systematic review has been performed combining the main Medical Subject Headings (MeSH) regarding the cell- and tissue-based therapies with the “Brain”, “Spinal Cord”, “Spine” and “Skull” MeSH terms. Only articles in English published in the last 10 years and pertinent to neurosurgery have been selected.ResultsA total of 1,173 relevant articles have been chosen. Somatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 209 publications
0
15
0
Order By: Relevance
“…Unlike other pathologies [24,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], the molecular mechanism underlying the pathophysiology of acquired coagulopathy is still not well known, although studies have reported that a few bioumoral parameters (pH, lactates, and BE) are significantly more compromised in trauma coagulopathy patients [24,32,48]. Because ours was not a pathophysiological study, we do not know whether this correlation stems from the fact that MT results more easily in coagulopathy or whether trauma coagulopathy increases the severity of the trauma itself or whether there is a mutual influence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other pathologies [24,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], the molecular mechanism underlying the pathophysiology of acquired coagulopathy is still not well known, although studies have reported that a few bioumoral parameters (pH, lactates, and BE) are significantly more compromised in trauma coagulopathy patients [24,32,48]. Because ours was not a pathophysiological study, we do not know whether this correlation stems from the fact that MT results more easily in coagulopathy or whether trauma coagulopathy increases the severity of the trauma itself or whether there is a mutual influence.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the coagulopathy is modified by trauma related factors such as brain injury and individual patient-related factors that include age, co-morbidities, and pre-hospital fluid administration [35][36][37]. A number of terms have been proposed to describe the specific trauma-associated coagulopathic physiology, including acute traumatic coagulopathy [19,38], early coagulopathy of trauma [29], acute coagulopathy of trauma-shock [27], trauma-induced coagulopathy [39], and trauma-associated coagulopathy [40].…”
Section: Physiological Criteria Anatomical Criteria Dynamic Criteriamentioning
confidence: 99%
“…Pai syndrome is also associated with various type of congenital nasal and facial anomalies involving the anterior skull base and meninges, caused by a maldevelopment of the embryonic mesenchyme, the latter having a paramount role in reparative processes of the central nervous system [ 15 , 16 ].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…All of these aspects made piezoelectric surgery an attractive option, in comparison with common rotating instruments, for human and veterinary procedures, everything in the context of the ongoing biotechnological revolution which has involved especially neurosurgery [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%